The Violence Reduction Programme: An exploration of posttreatment risk reduction in a specialist medium‐secure unit. (2nd September 2019) - Horgan, Harry; Charteris, Chloe; Ambrose, Derval
Abstract: Background: There is limited evidence for treatment programmes for offenders with a diagnosis of personality disorder deemed to be of high risk of violence towards others. Aim: This study sought to evaluate change in clinician‐rated risk of violence in males among offenders accepted to a specialist medium‐secure hospital providing treatment based on the Violence Reduction Programme (VRP). Method: A retrospective, records‐based cohort study design was used to explore change in risk of violence in a sample including five VRP cohorts composed of 33 offenders. Violence risk scale (VRS) score was the primary outcome measure. Correlates of treatment dropout were also explored. Results: Twenty‐seven men completed treatment. Paired pretreatment and posttreatment VRS scores were available for 19 men. Six men disengaged with treatment. There was a significant mean reduction in risk of violence score ( d = 1.08). At the individual level, eleven (57%) participants in the VRP showed reliable reduction in risk of violence. No treatment completers with a complete rating pair demonstrated an increased risk of violence. Younger age and referral from prison were significantly associated with treatment dropout. Conclusion: VRP‐based treatment appears to be a promising intervention for specialist services for offenders with a personality disorder diagnosis in the United Kingdom. Longer term follow‐up to ascertain whether these apparent treatment gains are accompanied by actual reduction in violent recidivism is now required, and a full scale trial warranted.